1993
DOI: 10.1093/brain/116.6.1509
|View full text |Cite
|
Sign up to set email alerts
|

The case of aphasia or neglect after striatocapsular infarction

Abstract: The occurrence of aphasia or neglect was related to anatomo-structural (CT/MRI), functional [regional cerebral blood flow (rCBF)] and pathogenetic features [duration of middle cerebral artery (MCA) occlusion and degree of cortical leptomeningeal anastomoses] in 57 cases (26 with and 31 without aphasia or neglect) with strictly subcortical infarcts of one defined type, i.e. striatocapsular infarcts. No distinct pattern of language disturbances was found. Aphasic syndromes did not differ in the amount of involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 0 publications
1
62
1
1
Order By: Relevance
“…However, the present results may be partly explained by several experimental and clinical studies. 2,3,6,7,[13][14][15][16] In experimental animals, transient MCAO leads to selective neuronal death and various glial responses without pannecrosis of the brain tissue in the ischemic region when reperfusion is instituted within a short period of time. 2,3,6,7 This selective neuronal loss advances from the striatum to the cerebral cortex in parallel with the prolongation of MCAO.…”
Section: Discussion Delayed Ischemic Hyperintensity On T1w Mri After Ssdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present results may be partly explained by several experimental and clinical studies. 2,3,6,7,[13][14][15][16] In experimental animals, transient MCAO leads to selective neuronal death and various glial responses without pannecrosis of the brain tissue in the ischemic region when reperfusion is instituted within a short period of time. 2,3,6,7 This selective neuronal loss advances from the striatum to the cerebral cortex in parallel with the prolongation of MCAO.…”
Section: Discussion Delayed Ischemic Hyperintensity On T1w Mri After Ssdmentioning
confidence: 99%
“…2,3,6,7 This selective neuronal loss advances from the striatum to the cerebral cortex in parallel with the prolongation of MCAO. In humans, several studies [13][14][15][16] suggest the presence of incomplete brain infarction after ischemia of either short or moderate severity. The incomplete infarction signifies an ischemic change with selective loss of some neurons and relative preservation of the integrity of the brain tissue structure.…”
Section: Fujioka Et Al 1999 1039mentioning
confidence: 99%
“…The idea that the underlying mechanism in the aphasias caused by basal ganglia lesions might be secondary cortical ischemia due to the occlusion of the internal carotid and its bifurcation (junction T) or the M1 portion of the middle cerebral artery 7,35 is highly provocative, and finds some support not only in the vascular anatomy, but also in the positive correlations between clinical improvement and involution of these hypoperfusion areas. Another important finding is the cortical atrophy encountered in MRI exams performed in later phases 34 . A question that emerged in our study, however, is related to the similar patterns of hypoperfusion found in the thalamic patients, that can not be primarily justified by ischemia, since thalamic lesions are frequently the result of injury in terminal arteries of the posterior circulation (vertebral-basilar system).…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
“…15,19,20 In support of this hypothesis, several studies have shown cortical hypoperfusion in patients with neglect associated with subcortical stroke using MR perfusion-weighted imaging or single photon emission computed tomography (SPECT). 15,19,21 It has been demonstrated that monkeys with unilateral lesions of nigrostriatal dopamine projections exhibited a persistent neglect of contralesional space. Rats with unilateral 6-hydroxydopamine injections destroying dopaminergic projection from the substantia nigra show a disturbance in space orientation, asymmetries in head position, and a change in response behavior to visual and tactile stimuli comparable to symptoms of neglect of contralateral stimuli.…”
mentioning
confidence: 96%
“…2,[11][12][13][14][15][16][17][18] Most of these studies examine patients with neglect as a consequence of stroke and it has been controversial if hemispatial neglect following subcortical lesions are the consequence of associated cortical dysfunction not visible by structural computer tomography or conventional magnetic resonance imaging (MRI). 15,19,20 In support of this hypothesis, several studies have shown cortical hypoperfusion in patients with neglect associated with subcortical stroke using MR perfusion-weighted imaging or single photon emission computed tomography (SPECT). 15,19,21 It has been demonstrated that monkeys with unilateral lesions of nigrostriatal dopamine projections exhibited a persistent neglect of contralesional space.…”
mentioning
confidence: 99%